Effect on total cholesterol levels of Sitagliptin in rats with induced diabetes - Rodríguez Vega, Juan Luis (2020)
Diabetes Mellitus (DM) is a syndrome of metabolic disorders with hyperglycemia, which produces an absolute or relative insulin deficiency. The effects of treatment of type II DM with Sitagliptin on lipid metabolism in general or particularly on homeostasis of body cholesterol have been scarcely studied. For this reason, the control of dyslipidemias in patients with type II DM is transcendental, the objective being: to determine the effect on total cholesterol levels of sitapgliptin, in Rattus rattus var. Albinus with streptozotocin induced diabetes. We followed an experimental, prospective longitudinal-sectional study, was selected 20 male albino rats; chosen at random, grouped into n = 10: Gl (Control group), with diabetes induced intraperitoneally in a dose of streptozotocin (40 mg / Kg) and G-II (experimental group), with diabetes induced with Streptozotocin (40mg / kg) and treated with 0.6% Sitagliptin. For measurements were used the Accutrend® Plus kit, which measures the intensity of the color produced in the reactive layer of the test strip, through reflectance photometry. In Group I, a slight increase in serum cholesterol concentration was observed and in Group II, there was a considerable increase in serum cholesterol concentration; according to 1, 5, 15 and 20 days of exposure at 95% confidence, with p <0.05 having statistical significance. Comparing the changes in serum concentration of total cholesterol, an increase in these levels was shown , as an adverse drug reaction of Sitagliptin.